Om at oversætte fra arabisk - Wulff, Ellen (Passage - Tidsskrift for litteratur og kritik, 2009)
Ellen Wulff: “Translating from the Arabic” This article deals with a translator’s problems when translating from the Arabic into Danish. The introduction presents the literary texts used as material and published in this edition of Passage, two chapters of the Libyan author Ibrahim al-Koni’s novel The Bleeding of the Stone. The first part discusses a translator’s difficulties due to disparity between grammatical structures in Semitic and Indo European languages, the second part difficulties due to divergent concepts of ‘good language’.